2008
DOI: 10.1111/j.1749-7345.2007.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Lipid Sources on the Survival, Growth, and Fatty Acid Composition of South American Catfish, Pseudoplatystoma fasciatum, Surubim, Juveniles

Abstract: The present study examines the effect of four semi‐purified diets (casein–gelatin based) where the source of fatty acids was free (esterified) oleic acid and linoleic acid (LA) (LOA diet), linseed and olive oil (predominantly LA and linolenic acid) (LO diet), cod liver oil (rich in highly unsaturated fatty acids) (CLO diet), and soybean lecithin (phospholipids; mostly LA) (LE diet) on the growth of juvenile South American catfish (surubim, Pseudoplatystoma fasciatum, Pimelodidae) (0.98 ± 0.04 g individual weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
5
24
0
2
Order By: Relevance
“…This research supports the results achieved in this study. Additional previous studies have also reported greater growth in the cases where dietary vegetable oils were used in place of fish oil in some fish species such as South American catfish (Arslan et al 2008), rainbow trout Oncorhynchus mykiss (Rinchard et al 2007), African catfish (Hoffman and Prinsloo, 1995;Ng et al 2003), and hybrid tilapia (Huang et al, 1998;Ng et al, 2001). In freshwater fish species, LA and LNA will fulfill the essential fatty acid requirements because freshwater fish have the ability to convert these fatty acids to longer chain n-3 and n-6 PUFA (Sargent et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This research supports the results achieved in this study. Additional previous studies have also reported greater growth in the cases where dietary vegetable oils were used in place of fish oil in some fish species such as South American catfish (Arslan et al 2008), rainbow trout Oncorhynchus mykiss (Rinchard et al 2007), African catfish (Hoffman and Prinsloo, 1995;Ng et al 2003), and hybrid tilapia (Huang et al, 1998;Ng et al, 2001). In freshwater fish species, LA and LNA will fulfill the essential fatty acid requirements because freshwater fish have the ability to convert these fatty acids to longer chain n-3 and n-6 PUFA (Sargent et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…Phospholipids are known to increase lipid utilization and their incorporation into enterocytes (Hadas et al, 2003). Several studies have reported that dietary soybean lecithin, a phospholipids source, had growth promoting effect in sea bass (Cahu et al, 2003), rainbow trout (Rinchard et al, 2007), carp Cyprinus carpio (Geurden et al, 1997), and South American catfish (Arslan et al, 2008). In rainbow trout, fish fed a diet with lecithin as the primary dietary lipid source had significantly higher growth performance than those fed a diet with fish oil in water temperatures ranging from 15 to 19 o C (Rinchard et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…channel catfish (Stickndy and Andrews, 1972), African catfish (Ng et al, 2003) 및 South American catfish (Pseudoplatystoma fasciatum) (Arslan et al, 2008)에서도 본 연구와 유사한 지방산 변화 경향을 보였다. 이러한 결과는 담수어인 메기는 체내에 서 18:2n-6을 20:4n-6 및 22:4n-6으로, 18:3n-3을 20:5n-3 및 22:6n-3으로 전환할 수 있기 때문인 것으로 알려져 있다 (Yamada et al, 1980;Kissil et al, 1987).…”
unclassified
“…Some research has been performed to improve the knowledge on physiology (Arslan et al, 2008;2009;Noffs et al, 2009) and nutrition (Gonçalves and Carneiro, 2003;Teixeira et al, 2010) of surubim juveniles. However, there are still gaps in the information that need to be filled regarding the rearing system and nutrient utilization.…”
Section: Introductionmentioning
confidence: 99%